(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Irritable bowel syndrome (IBS) is defined as a chronic disorder of gut–brain interaction characterized by recurrent abdominal pain and associated disturbances in bowel habits. The prevalence of IBS in the general population ranges from 1.5% to 10.1%, depending on geographic region and the diagnostic criteria used. The negative impact of IBS on patients’ quality of life is widely recognized and is associated with dietary restrictions, limitations in daily and social activities, interpersonal relationships, as well as a significant socioeconomic burden. This burden is largely due to the relatively low effectiveness of existing therapeutic strategies.